THE DEVELOPMENT OF THE QUALITY OF CLASSROOM ACTION RESEARCH EVALUATION MODEL OF TEACHING PRACTICUM STUDENTS, FACULTY OF EDUCATION, INSTITUTE OF PHYSICAL EDUCATION BY PARTICIPATORY ACTION RESEARCH - Kachayut , Kamonwan; jiraro , Pongthep; Haenjohn, Juthamas (Academic Journal of Thailand National Sports University, 2019)
Classroom action research were a searching process for solutions to the problems while teaching. The study of the condition for development of the quality of classroom action research evaluation model were appropriate. Could be used to a feedback to improve quality classroom action research. It could develop student classroom action research skills. The results of the research can be used to solve problems and develop effective learning in the classroom. The objectives of the research were to: 1) study the state of the quality evaluation for classroom action research of teaching practicum students, Faculty of Education, Institute of Physical Education. The data were collected by questionnaire on state of the research quality in knowledge, concepts and practices. the samples were 991 mentors and supervisors, Faculty of Education in the year 2017 together with related documents, analyzing the quantitative data, content analyzing, and conclusion 2) develop a quality evaluation model for classroom action research of teaching practicum students, Faculty of Education Institute of Physical Education by participatory action research. The model was verified by 17 experts. Using formative and model critical forms as the data collection tools. The data were analyzed by median and interquartile range 3) Evaluate the effectiveness of the developed quality evaluation model by participatory action research. The data were collected by the effectiveness evaluation forms. The implementation group were the supervisors. The data were analyzed by descriptive statistics. The analysis results were; There were 3 components and 20 indicators of the quality evaluation for classroom action research. For the indicators, they were; the classroom action research process, research operation, and the apply of classroom action research. The evaluation result by experts found that the model was most appropriate and was congruent with the overall criteria. The results of the comparison of knowledge and concept were that the post implementation score were higher than pre implementation score statistically significant at .05 level. For the 4 dimensions an evaluation by Stufflebeam's (2001) theory, it was higher than 3.50 in overall standard, indicating that the model had quality and could be used in the classroom